The role of TikTok in the second round of the 2023 Ecuadorian elections - Gutiérrez Alvarado, Mariú Dessiré (2025)
The digitalization of political communication has positioned emerging platforms such as TikTok at the center of electoral campaigns. This article aims to analyze the role of TikTok as a political communication platform during the second round of the 2023 Ecuadorian presidential elections. A mixed methodology was employed, combining quantitative and qualitative content analysis through a validated coding matrix, and all official publications by the candidates during the electoral period were processed. The results show that Noboa relied on viral trends that generated greater reach and interaction, while González opted for more traditional formats, achieving broader organic redistribution. In both cases, the proportion of informative content was minimal. The discussion highlights the consolidation of algorithmic persuasion models and politainment, in which emotionality and spectacularization prevail over rational deliberation. The dynamics of TikTok during this electoral period revealed the primacy of persuasive and emotional content over informative content, which reinforces politainment but poses risks for democratic deliberation and the formation of critical citizenship.